Hukum Kontrak di Era Digital: Adaptasi Teknik Pembuatan Kontrak dalam Transaksi Online - Maulia Nurfadillah (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to examine the role of law in the development of digital technology that has driven the transformation of traditional contracts into online contracts, which enable fast and easily accessible transactions. However, these digital contracts present new challenges related to legal certainty, especially in the aspects of electronic agreement, privacy protection, and data security. Based on this, this study discusses the importance of adapting contract-making techniques in the digital era to maintain the rights and legal certainty of the parties. Based on a normative legal approach, this article shows that digital contracts require specific elements such as valid electronic agreement, comprehensive privacy protection clauses, and the determination of applicable laws in various jurisdictions. With adaptive contract-making techniques, the risk of disputes can be reduced, and legal certainty in online transactions can be increased